PENGARUH BELANJA PEMERINTAH UNTUK PENDIDIKAN, KESEHATAN DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Royda, Royda (Jurnal Integritas Serasan Sekundang, 2022)
The objective of this research is analyzing how government.s expenditure on education, health and infrastructure influence economic growth in cities of Sumatera Selatan Province. The government.s expenditures on education, health and infrastructure are basically investments on economic growth.The effect of the development on those three sectors has no direct impact but it requires several periods to feel the after effects. The model used are panel regression data, with independent variable is education expenditure, health expenditure, infrastructure expenditure, and dependent variable is economic growth. This study conducted in 15 cities and districts of Sumatera selatan province and then data taken from 2008 to 2013. The end result showing is that education expenditure have negative influence, health expenditure have positive and significantly affect the economic growth. Then, as for the infrastructure expenditure variable showing negative influence and significantly affect the economic growth